Perinatal Outcome in Relation to Chorionicity in Twin Pregnancy - Machado, Marta (2017)
Introduction: The incidence of multiple gestations is increasing worldwide and many studies have shown higher perinatal morbidity and mortality rates in monochorionic twins compared to dichorionic. The aim of this study was to assess the twin population born at a tertiary center and to evaluate the impact of chorionicity on perinatal outcomes of twin pregnancies.Material and Methods: Retrospective study of all twins born in a tertiary center from January 2004 to December 2013.Results: In this period, 1051 twins were born, related to 540 gestations (26.7% monochorionic; 73.3% dichorionic). There was no statistical significant difference between the groups concerning obstetric complications. The monochorionic group had a higher incidence of intrauterine growth restriction (20.5 vs 11.3%, p < 0.001), lower mean maternal age (29.9 vs 31.9 years, p < 0.001), lower mean gestational age (33.4 vs 34.3 weeks, p < 0.05) and lower mean birth weight (1943 vs 2147 g, p < 0.001). Monochorionic twins had a higher incidence of hyaline membrane disease (7 vs 4%, p < 0.05), sepsis (10.3 vs 5.8%, p < 0.05) and anemia (9.5 vs 5.4%, p < 0.05). There were no statistical significant differences concerning necrotizing enterocolitis, intraperiventricular hemorrhage or retinopathy of prematurity. Perinatal mortality was higher in the monochorionic group (5.2 vs 2.9%, p < 0.05).Discussion: Monochorionic twins represent considerable challenges to both obstetricians and neonatologists and should be monitored and delivered at tertiary centers.Conclusion: Currently gemelarity has a major impact on total births. It would be interesting to develop protocols to standardize clinical approach to twins.